Compromised redox homeostasis, altered nitroso-redox balance and therapeutic possibilities in atrial fibrillation - Simon, J; Ziberna, K; Casadei, B (Oxford University Press, 2016)
Although the initiation, development and maintenance of atrial fibrillation (AF) has been linked to alterations in myocyte redox state, the field lacks a complete understanding of the impact these changes may have on cellular signalling, atrial electrophysiology, and disease progression. Recent studies demonstrate spatiotemporal changes in reactive oxygen species production shortly after the induction of AF in animal models with an uncoupling of nitric oxide synthase activity ensuing in the presence of long-standing persistent AF, ultimately leading to a major shift in nitroso-redox balance. However, it remains unclear which radical or non-radical species are primarily involved in the underlying mechanisms of AF, or which proteins are targeted for redox modification. In most instances, only free radical oxygen species have been assessed, yet evidence from the redox signalling field suggests that non-radical species are more likely to regulate cellular processes. A wider appreciation for the distinction of these species and how both species may be involved in the development and maintenance of AF could impact treatment strategies. In this review we summarize how redox second-messenger systems are regulated, and discuss the recent evidence for alterations in redox regulation in the atrial myocardium in the presence of AF, while identifying some critical missing links. We also examine studies looking at antioxidants for the prevention and treatment of AF and propose alternative redox targets which may serve as superior therapeutic options for the treatment of AF.